Effect of treatment with an overheated dry-saturated steam vapour disinfection system on multidrug and extensively drug-resistant nosocomial pathogens and comparison with sodium hypochlorite activity. (December 2015) - Bagattini, Maria; Buonocore, Raffaella; Giannouli, Maria; Mattiacci, Dario; Bellopede, Rossella; Grimaldi, Nicola; Nardone, Antonio; Zarrilli, Raffaele; Triassi, Maria
Abstract Background The development of portable steam generators has made disinfection of the environment more practical. This study assessed the "in vitro" ability of an overheated dry-saturated steam vapour system to kill multidrug and extensively-drug resistant nosocomial pathogens, defining the antimicrobial spectrum and the contact times compared with the activity of sodium hypochlorite. Methods The antibacterial efficacy of the overheated dry-saturated steam vapour system and of sodium hypochlorite against nosocomial pathogen isolates: extensively drug-resistantAcinetobacter baumannii, Pseudomonas aeruginosa, carbapenemase-producingKlebsiella pneumoniae, methicillin-resistantStaphylococcus aureus, high-level aminoglycoside-resistantEnterococcus faecalis, Candida parapsilosis andAspergillus fumigatus were assessed using a surface time-kill test carried out on glass surfaces, with or without bovine serum albumin (BSA). Results The bactericidal activity of the overheated dry-saturated steam vapour system was observed at 180 °C after 5 min contact with or without BSA, using an initial inoculum of 109 CFU/mL. To reduceC. parapsilosis andA. fumigatus counts (from 107 CFU/mL), a longer contact time was necessary (7 min). In vitro tests with sodium hypochlorite at 5 % in the absence of an organic substance also resulted in an overall reduction in bacterial counts (from 109 CFU/mL) after 5 min of treatment. For mycotic challenge (107 CFU/mL), a longer contact time was necessary (7 min). In the presence of an organic substance, after 5 min, the hypochlorite reduced the viable count from 109 to 105 CFU/mL for all bacterial strains exceptE. faecalis that showed a reduction of 2 log units (109 to 107 CFU/mL). ForC. parapsilosis andA. fumigatus, a 2 log unit reduction was observed after 7 min. Conclusions Steam disinfection of environmental surfaces using a portable steam generator is a practical and effective method that is not affected by the presence of organic matter.